The Relationship between Nutritional Status and the Productivity of Production Workers - Bara, Inggrid Mentari Batu; Susanti, Nofi; Salianto, Salianto (Indonesian Journal of Global Health Research, 2024)
The industrial sector is a significant contributor to employment in Indonesia, necessitating the availability of skilled and competent workers. Enhancing worker productivity is crucial for companies to remain competitive, as it allows for the production of goods within predetermined proportions in a shorter timeframe. Productivity among workers is influenced by various factors, notably their nutritional status and health. This study aims to explore the relationship between nutritional status and productivity among production workers at Pt. Wijaya Karya Beton Tbk Ppb in North Sumatra. The research employs a quantitative approach with a cross-sectional study design, involving a sample of 63 workers from a total of 410 in the production department. Data collection tools included scales and microtoise for height measurement, with data analysis conducted using the chi-square test at a 95% confidence level (α = 0.05). The study found that out of the 63 workers, 27 (42.9%) were classified as productive, while 36 (57.1%) were deemed unproductive. The chi-square test results indicated a significant relationship between nutritional status and worker productivity (P value = 0.049). The study concludes that nutritional status significantly affects labor productivity, with normal nutritional status being a key factor in enhancing work performance.